Culprit-Only Versus Complete Revascularization in STEMI Multi-Vessel Disease: A Case Report - Mega Amanda Putri; Achmad Fauzi Yahya; Triwedya Indra Dewi (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To revisit data and highlight management of STEMI multi-vessel disease and explore culprit-only versus multi-vessel PCI and optimal timing to achieve complete revascularization.Methods: A 67 years old male with chest pain at rest 2 hours before admission with a history of smoking one pack of cigarette every day, was presented to the hospital. Physical examination was within normal limit with normal hemodynamically; however, elevated cardiac troponin was identified. Electrocardiogram showed STEMI anteroseptal wall with ischemic inferior wall, leading toSTEMI anteroseptal wall, Killip I diagnosis. Primary PCI was performed and multi-vessel disease was found. A complete revascularization single-staged procedure was performed due to his persistent chest pain. PCI of these coronary stenoses is beneficial to reduce risk of cardiac death and recurrent infarction. However, some issues related to PCI of non-culprit coronary arteries lesion and optimal timing to do complete revascularization is still a dilemma. Results: Related to data from some trials, e.g PRAMI, CvLPRIT, DANAM-3-PRIMULTI, COMPARE-ACUTE, COMPLETE, and some meta-analyses, showed benefit and safety of routine PCI of non-culprit lesions as a preventive strategy to reduce morbidity and mortality. Data showed reduce future morbidity and mortality in this setting. Meanwhile, the optimal timing of complete revascularization is still a matter of debate, although some data showed benefit of index procedural PCI.Conclusion: PCI of non-culprit lesions of myocardial infarction is consistently beneficial over culprit-only revascularization in patients with STEMI multi-vessel disease, despite the debate on the optimum timing for complete revascularization in this setting.